Panduri Berseri Ecotourism: Corporate Social Responsibility Program by Fuel Terminal Tuban to Community Empowerment in Tasikharjo Village Tuban - Hasfin Bagus Trianto; Affrida Eka Ramadhany; Sukmayadevi; Maulida Nur Faticha; Shinta Tris Irawati (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The Panduri Berseri Ecotourism Program is one such initiative Corporate Social Responsibility (CSR) which is run by PT Pertamina Patra Niaga Fuel Terminal (FT) Tuban. This program was implemented in Tasikharjo Village, Jenu District, Tuban Regency, East Java Province. Tasikharjo Village is located on the north coast and has beach potential. This potential has encouraged local communities to conserve and manage their natural assets to preserve the environment and develop new economic potential by managing beaches as tourist destinations. This research examines the process of implementing the CSR program by PT Pertamina FT Tuban. CSR program by PT Pertamina FT Tuban implemented trought stages of planning, implementation, monitoring and evaluation. The approach used is Participatory Rural Appraisal (PRA), which involves active community participation in every step of program implementation. The implementation of CSR from PT Pertamina FT Tuban through the Panduri Berseri program provides benefits for encouraging environmental sustainability and for the economic sustainability of the Tasikharjo Village community Keywords: Ecotourism, Empowerment, Community, Corporate Social Responsibility, and PT. Pertamina Patra Niaga Fuel Terminal Tuban